2009
DOI: 10.2174/157339909787314121
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Bevacizumab for Diabetic Retinopathy

Abstract: Diabetic retinopathy (DR) remains the major threat to sight in the working age population. Diabetic macular edema (DME) is a manifestation of DR that produces loss of central vision. Macular edema within 1 disk diameter of the fovea is present in 9% of the diabetic population. Proliferative diabetic retinopathy (PDR) is a major cause of visual loss in diabetic patients. In PDR, the growth of new vessels from the retina or optic nerve, is thought to occur as a result of vascular endothelial growth factor (VEGF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 45 publications
3
32
0
11
Order By: Relevance
“…24 Anti-VEGF treatment and safety Dosage and frequency of anti-VEGF treatment in PDR cases The optimal dose and dosing sequence for bevacizumab remains unclear. Most studies have used a dose of 1.25 mg. [25][26][27][28][29] Arevalo and Garcia-Amaris 30 used dosages of 1.25 mg (20.5%) and 2.5 mg (79.5%) bevacizumab, depending on the discretion of the treating clinician, and noted that the 2.5-mg dose was more effective in inducing complete regression of neovascularization relative to the 1.25-mg dose in the treatment of naive eyes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Anti-VEGF treatment and safety Dosage and frequency of anti-VEGF treatment in PDR cases The optimal dose and dosing sequence for bevacizumab remains unclear. Most studies have used a dose of 1.25 mg. [25][26][27][28][29] Arevalo and Garcia-Amaris 30 used dosages of 1.25 mg (20.5%) and 2.5 mg (79.5%) bevacizumab, depending on the discretion of the treating clinician, and noted that the 2.5-mg dose was more effective in inducing complete regression of neovascularization relative to the 1.25-mg dose in the treatment of naive eyes.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies deferred re-injections to cases that only showed recurrence. 30 Effectiveness of dose 1.25 mg bevacizumab at regression of neovascularization: level of evidence IV.…”
Section: Methodsmentioning
confidence: 99%
“…12 The possibilities for retarding disease progression including recent advances in pharmacologic management of diabetic maculopathy, best applied at the earliest stages of the development of abnormal pathology, further increase the priority that should be afforded to effective disease monitoring. [13][14][15] Diabetic maculopathy is the most common cause of visual loss in diabetic patients. Visual acuity represents the most widely used test of visual, and in particular macular, function.…”
Section: Suitability and Repeatability Of A Photostress Recovery Testmentioning
confidence: 99%
“…In ophthalmology, the use of bevacizumab has grown due to its significant lower price when compared with the previous molecules. Its use in diabetic retinopathy has also grown with promising results in proliferation and macular edema [111][112][113] and in the clearing of vitreous hemorrhages [114]. It has shown effectiveness in neovascular glaucoma secondary to ischemic retinal diseases including diabetic retinopathy [37].…”
Section: Anti-vegf Therapymentioning
confidence: 99%
“…This is especially important in situations of vitreous hemorrhage. Even though some authors use intravitreal bevacizumab as the first line agent in selected cases of diabetic retinopathy [113] including diabetic macular edema [13], it is still early to recommend at the moment, anti-VEGF therapy without laser therapy outside clinical trial settings.…”
Section: Anti-vegf Therapymentioning
confidence: 99%